G1 cyclin-dependent kinases are insufficient to reverse dE2F2-mediated repression - Frolov, Maxim V. (Cold Spring Harbor Laboratory Press, 2003)
Here we show that the cell cycle defects of dE2F1-depleted cells depend on the cooperative effects of dE2F2 and DACAPO (DAP), an inhibitor of Cyclin E/cyclin-dependent kinase 2 (CycE/cdk2). The different properties of cells lacking dE2F1/dE2F2 and dE2F1/DAP lead to the surprising observation that dE2F2-mediated repression differs from retinoblastoma family protein 1 (RBF1) inhibition of dE2F1, and is resistant to both CycE/cdk2 and Cyclin D/cyclin-dependent kinase 4 (CycD/cdk4). This resistance occurs even though dE2F2/RBF1 complexes are disrupted by CycE/cdk2, and may explain why dE2F2 is so potent in the absence of de2f1. The implication of these results is that cells containing dE2F2 require dE2F1 to either prevent, or reverse, dE2F-mediated repression.